Case report: Curative effect and mechanism of surufatinib combined with toripalimab in the treatment of 1 case of lung large-cell neuroendocrine carcinoma - Xiong, Shuanglong; Yang, Chengxiang; Fu, Kaiwen; Liao, Xingyun; Ding, Yao; Zhou, Kexue; Zhang, Li; Teng, Yan; Wu, Chunman; Li, Yongsheng; Liang, Houjie; Li, Yan (Frontiers in Oncology, 2025)
BackgroundLarge-cell neuroendocrine lung carcinoma (LCNEC) is a rare heterogeneous tumour with rates ranging from 2.1% to 3.5%. The overall prognosis of pulmonary LCNEC is poor, and the 5-year overall survival rate is only 21%. Advanced LCNEC treatment drugs are limited, and their efficacy is low. Here, we report a case of advanced lung LCNEC treated with front-line chemotherapy, which significantly delayed tumour progression after combined therapy with targeted immunotherapy. Moreover, we explore the mechanism of the correlation between dynamic changes in the immune microenvironment and therapeutic effects.Case presentationWe describe a patient with advanced pulmonary LCNEC who achieved disease remission and progression-free survival (PFS) of up to 15.1 months after chemotherapy with first-line EP and second-line FOLFIRI. In February 2022, this patient, a 58-year-old male, was diagnosed with left lung large-cell neuroendocrine carcinoma. The initial stage was cT1N2M1aIVA (right lung); however, the disease progressed after 6 cycles of EP chemotherapy, and the revised diagnosis was left lung large-cell neuroendocrine carcinoma, stage cT4N3M1a IVA (right lung). The patient participated in the “randomized, open, multicentre phase III clinical study to evaluate the efficacy and safety of solantinib combined with toripalimab versus FOLFIRI as second-line treatment for advanced neuroendocrine carcinoma”, and the efficacy of the FOLFIRI regimen was evaluated after 4 cycles of chemotherapy for PD. The best results were a partial response (PR) and a PFS of up to 15.1 months.ConclusionThis case confirmed the efficacy of ICI therapy against TMB-H lung large-cell neuroendocrine carcinoma, suggesting that the immune microenvironment and TMB analysis are helpful for guiding the personalized treatment of LCNEC.